Schizencephaly Associated with Congenital Cytomegalovirus Infection (Revista de Medicina Clinica, 2023)
Clinical snapshot on "Schizencephaly Associated with Congenital Cytomegalovirus Infection" presented in volume 7 issue 1 of 2023 of Revista de Medicina Clínica.
Keywords: Schizencephaly; Cytomegalovirus; Seizures